2018
DOI: 10.1038/s41598-018-21799-8
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell type-specific changes in spinal dipeptidyl peptidase 4 expression and effects of its inhibitors in inflammatory and neuropatic pain

Abstract: Altered pain sensations such as hyperalgesia and allodynia are characteristic features of various pain states, and remain difficult to treat. We have shown previously that spinal application of dipeptidyl peptidase 4 (DPP4) inhibitors induces strong antihyperalgesic effect during inflammatory pain. In this study we observed low level of DPP4 mRNA in the rat spinal dorsal horn in physiological conditions, which did not change significantly either in carrageenan-induced inflammatory or partial nerve ligation-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…17 Kiraly et al reported that the expression of the DPP4 protein was increased by peripheral inflammation in astrocytes and also after neural injury (partial ligation of the sciatic nerve) in microglia suggesting that in pathological painful situations the role of DPP4 becomes more pronounced, therefore the effect of DPP4 inhibitors on nociception could also increase. 18 They reported that DPP4 inhibitors could activate the endogenous opioid system and cause an opioid-mediated anti-hyperalgesic effect in subacute inflammatory pain. Similarly, Balogh et al, in their study on rat inflammatory pain models reported that the anti-hyperalgesic effect of DPP4 inhibitors can be attributed to the activation of endogenous opioid system especially the delta opioid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…17 Kiraly et al reported that the expression of the DPP4 protein was increased by peripheral inflammation in astrocytes and also after neural injury (partial ligation of the sciatic nerve) in microglia suggesting that in pathological painful situations the role of DPP4 becomes more pronounced, therefore the effect of DPP4 inhibitors on nociception could also increase. 18 They reported that DPP4 inhibitors could activate the endogenous opioid system and cause an opioid-mediated anti-hyperalgesic effect in subacute inflammatory pain. Similarly, Balogh et al, in their study on rat inflammatory pain models reported that the anti-hyperalgesic effect of DPP4 inhibitors can be attributed to the activation of endogenous opioid system especially the delta opioid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…After determination of the time of peak effect further analysis was made at that time point. An animal was considered neuropathic, when the PPT value was at least decreased by 20% compared to weight match animals as described previously (Király et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…MERS-CoV has the potential ability to enter microglia, astrocytes, and neurons, considering that all these cell types express DPP4 ( Király et al., 2018 ; Elkjaer et al., 2019 ). Among these CNS cells, glial fibrillary acidic protein-positive (GFAP+) astrocytes seem to show the largest DPP4 basal expression, and inflammation significantly increased the expression of the viral receptor ( Király et al., 2018 ), thus allowing a feed-forward loop that increases MERS-CoV access to glial cells. Moreover, DPP4 was also found in brain microvasculature ( Kenny and Bourne, 1991 ; Zeng et al., 2019 ) turning endothelial cells into another MERS-CoV potential target.…”
Section: Middle East Respiratory Syndromementioning
confidence: 99%